Edukasi Bantuan Hidup Dasar pada Santriwati Pondok Pesantren Imam As-Syafi’I Genteng - Yuanto, Hirdes Harlan; Rahmawan, Fajri Andi; Toga, Erik; masroni, Masroni; Wijiastutie, Ida Srisurani (Journal of Health Innovation and Community Services, 2022)
Background: Daily emergency health services are a human right of everyone and an obligation that everyone should have. The government and the entire community are responsible for maintaining and improving the quality of health services. In everyday circumstances, the handling of emergency patients will involve pre-hospital services, services in hospitals and services between hospitals, so an integrated daily emergency management system is needed. Based on the results of the study at the Imam As-Syafi'I Genteng Islamic Boarding School, from interviews with disaster management volunteers, data was obtained that the volunteers at the Imam As-Syafi'I Genteng Islamic Boarding School were classified as volunteers who lacked knowledge deficits related to first aid in accidents because they had never received first aid education and training for emergency patients. Based on data obtained from one of the administrators and participants at the Imam As-Syafi'I Genteng Islamic Boarding School, they have never been given counseling related to material on basic life support (BHD), shelter and how to transport emergency patients as a provision for first aid in an accident. The purpose: of this community service is for students to know and understand about basic life support. Method: this community service uses BHD material counseling and then practice using mannequins. Result: This program activity has increased the knowledge of female students about basic life support. Conclusion: Community service carried out through the presentation of material and direct practice to mannequins not only provides new insights to students but can also provide their own experiences for students in carrying out basic life support.